Zafar Abbas ki”Bazgasht e Iqbal”aik Mutalia: ظفر عباس کی " بازگشتِ اقبالؔ "ایک مطالعہ - Khattak, Professor Dr. Irfan Ullah (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Iqbal’s personality, his work, and his message are so great and enchanting that it had captivated the world since long and it seems difficult to escape from his bewitching artistic strokes. Iqbal’s poetry is universal and divine. It’s misapprehension to assimilate the sublimity of his poetic imagination and then keep on soaring high with it. However, there exist a few admirers of Iqbal who transcends these limits and felt the depth of his poetry, resulting in authoring a book "Bazgasht-e-Iqbal" by Zafar Iqbal. In this literary work, he chose sixty poems of Iqbal for " TAZMEEN" - an Urdu literary genera in which one or two lines of an original stanza of a poem are replaced with corresponding lines by some other poet. He made an attempt (deliberate or accidental) to present Iqbal’s grand style and diction which display a fine blend of Urdu and Persian languages without marring the spirit. He rendered a great service by further elaborating Iqbal’s poetic philosophy like ’Khudi’ ’ Sifat-e-Shaheeni’, ’Rasm-e-Shabbiri’ etc. No doubt it’s a laudable effort by the author to discover new aspects of Iqbal’s poetic thought. This literary work will prove a valuable addition for our youth in understanding Iqbal’s literary work and his thought.